2008
DOI: 10.1007/s10911-008-9076-6
|View full text |Cite
|
Sign up to set email alerts
|

HER4 Intracellular Domain (4ICD) Activity in the Developing Mammary Gland and Breast Cancer

Abstract: The HER4 receptor tyrosine kinase was the final member of the EGFR-family to be discovered. In contrast to the other three members of this receptor family which function primarily as mitogenic effectors in the breast, HER4 appears to have multiple divergent functions in the normal and malignant breast. Interestingly, the majority of HER4 activities in the breast including pregnancy induced differentiation and lactation initiation, transcriptional activation, tumor cell proliferation, growth suppression, and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
81
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(85 citation statements)
references
References 64 publications
3
81
0
Order By: Relevance
“…It is clear that ErbB-4 is functionally involved in mammary development in the animal (Jones 2008). ErbB-4 nuclear localization has been observed in normal and tumor mammary tissue and exogenous ICD expression provokes differentiation events (Muraoka-Cook et al 2006).…”
Section: Secretase Processing Of Rtks Erbb-4 Receptormentioning
confidence: 99%
“…It is clear that ErbB-4 is functionally involved in mammary development in the animal (Jones 2008). ErbB-4 nuclear localization has been observed in normal and tumor mammary tissue and exogenous ICD expression provokes differentiation events (Muraoka-Cook et al 2006).…”
Section: Secretase Processing Of Rtks Erbb-4 Receptormentioning
confidence: 99%
“…The functional significance of this is controversial [39]. The HER4 receptor appears to possess divergent functions demonstrated in vitro to depend on the isoform of the receptor [40] [41]. The HER4 response can also depend on the activating ligand [42], or the localization in the cell compartments (membrane bound, cytoplasmatic or in the nucleus) [43].…”
Section: Discussionmentioning
confidence: 99%
“…The BH3-only protein acts as a 'sensor' of apoptosis stimulation and is regarded as a necessary effective factor for initiating apoptosis. Naresh et al (2006) found that HER4 intracellular domain (4ICD) of ErbB4 is a BH3-only protein that can promote the apoptosis of breast cancer cells; Jones (2008) found that the notch intracellular domain of ErbB4 activates the growth of mammary tissue and improves the occurrence of breast cancer and apoptosis of breast cancer cells. However, the specific action mechanism by which the ErbB4 intracellular region involved in regulation remains unclear.…”
Section: Introductionmentioning
confidence: 99%